2019
DOI: 10.2147/amep.s210557
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of academic performance in medical students: evidence from a medical school in south-east Nigeria</p>

Abstract: Background Medical education is considered one of the toughest college degrees to acquire. Exploring the factors that determine good academic performance in medical school will help in the planning of curriculum and assist students to navigate through medical school more effectively. Methods This cross-sectional and descriptive study enrolled 145 second year clinical students (500 level) of the Enugu State University of Science and Technology in south-east Nigeria using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
2
5
1
1
Order By: Relevance
“…Even though food and dormitory services are provided to the students by the university, students need money for jaunts, stationaries, to buy dressings, and other necessities. However, the current result is contrary to the study done in Southeast Nigeria [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Even though food and dormitory services are provided to the students by the university, students need money for jaunts, stationaries, to buy dressings, and other necessities. However, the current result is contrary to the study done in Southeast Nigeria [19].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, in Pakistan, joining the medical profession was significantly linked with good academic scores [ 13 ]. Admission to medical school was also a significant predictor of good academic performance in Nigeria [ 32 ]. Additionally, in Southern Ethiopia, poor academic performance was significantly higher among agriculture students than health science students [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ekwochi et al performed a study in 2018 to evaluate the determinants of academic performance in medical students in Nigeria. They stated that better time management between extracurricular activities and devoted time for studying would likely result in better academic performance [ 27 ]. Shawwa et al also shared the same observation in a study conducted at the Faculty of Medicine of King Abdulaziz University in October 2012 and found that students who spent more than 2 hours per day studying recorded a better GPA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%